"And it snowballed from there": The development of orthorexia nervosa from the perspective of people who self-diagnose. (1st December 2020) - Valente, Martina; Brenner, Rachel; Cesuroglu, Tomris; Bunders-Aelen, Joske; Syurina, Elena V.
Abstract: This study aims to include the perspective of those who share content about Orthorexia Nervosa (ON) on Instagram and self-diagnose with ON (SD-ON) to trace their development of ON, gain insights into risk factors, symptoms and recovery, and explore differences with those who do not SD-ON. This research used mixed methods, with a sequential explanatory design. The quantitative component (n = 185) aimed to identify biological, psychological, interpersonal, and contextual factors that play a role in each phase of ON development. The qualitative component (n = 10) aimed to probe how and why individuals who SD-ON feel that certain experiences have shaped their development of ON. Respondents defined ON an obsession with healthy eating and clean or pure foods, with unhealthy effects on physical, mental or social wellbeing. A minority of participants did not view ON as problematic, but as a "salvation" from chronic diseases. Three phases characterizing the development of ON were identified: onset, progression and help seeking. Regarding the onset, two routes were identified, both characterized by a snowball effect of interacting factors. Regarding the progression of ON, several symptoms were identified, with obsession with healthy eating being the most frequent one. The majority of participants were trying to lose weight during ON, but their rationale was health rather than appearance. Regarding the help-seeking phase, reasons for problem realization were identified. ON was not noticed by loved ones until major health problems occurred, this being a barrier for recovery. While most believed that recovery is possible, respondents agreed that ON is a condition that will always linger in the back of the mind. This study contributes to addressing the shortage of qualitative studies investigating ON from insiders' perspective.